ANALISIS BERPIKIR SISWA KELAS VII SMP BERDASARKAN TEORI VAN HIELE DALAM MENYELESAIKAN SOAL PADA MATERI SEGITIGA - Wahyuni, Elsa; Laurens, Theresia; Rumalean, Muhammad Samad (Atom : Jurnal Riset Mahasiswa, 2023)
Abstract This research aims to describe the thinking of class VII students at SMP Negeri 21 Ambon based on Van Hiele's theory in solving problems on triangle material. Types of research, namely qualitative research. The subjects in this research were 3 selected students of 21 students provided that students answer all questions correctly and students who are able to communicate according to the teacher's considerations that school. The qualitative data analysis used consists of data reduction, data presentation and drawing conclusions. The research results show that for level 0 (visualization) the three subjects have fulfilled level 0, namely being able to describe something build on its properties and use the description to draw a shape. For level 1 (analysis) all three subjects have fulfilled level 1, namely being able to say they are awake flat what is formed based on given properties. And level 2 (sorting) All three subjects have fulfilled level 2, namely being able to identify information that is known and asked from the question and can be use the right strategy and get the right answer